Genetic diversity and population genetic structure in the South African commercially important shark species, the common smoothhound (Mustelus mustelus) - Maduna, Simo Njabulo (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.